The Class II Trehalose 6-phosphate Synthase Gene PvTPS9 Modulates Trehalose Metabolism in Phaseolus vulgaris Nodules - Barraza, Aarón; Contreras-Cubas, Cecilia; Estrada-Navarrete, Georgina; Reyes, José L.; Juárez-Verdayes, Marco A.; Avonce, Nelson; Quinto, Carmen; Díaz-Camino, Claudia; Sanchez, Federico (Frontiers in Plant Science, 2016)
Legumes form symbioses with rhizobia, producing nitrogen-fixing nodules on the roots of the plant host. The network of plant signaling pathways affecting carbon metabolism may determine the final number of nodules. The trehalose biosynthetic pathway regulates carbon metabolism and plays a fundamental role in plant growth and development, as well as in plant-microbe interactions. The expression of genes for trehalose synthesis during nodule development suggests that this metabolite may play a role in legume-rhizobia symbiosis. In this work, PvTPS9, which encodes a Class II trehalose-6-phosphate synthase (TPS) of common bean (Phaseolus vulgaris), was silenced by RNA interference in transgenic nodules. The silencing of PvTPS9 in root nodules resulted in a reduction of 85% (± 1%) of its transcript, which correlated with a 30% decrease in trehalose contents of transgenic nodules and in untransformed leaves. Composite transgenic plants with PvTPS9 silenced in the roots showed no changes in nodule number and nitrogen fixation, but a severe reduction in plant biomass and altered transcript profiles of all Class II TPS genes. Our data suggest that PvTPS9 plays a key role in modulating trehalose metabolism in the symbiotic nodule and, therefore, in the whole plant.